The QCD axion from aligned axions and diphoton excess - Tetsutaro Higaki; Kwang Sik Jeong; Naoya Kitajima; Fuminobu Takahashi (Physics Letters B, 2016)
We argue that the QCD axion can arise from many aligned axions with decay constants much smaller than the conventional axion window. If the typical decay constant is of O(100) GeV to 1 TeV, one or more of the axions or saxions may account for the recently found diphoton excess at ∼750 GeV. Our scenario predicts many axions and saxions coupled to gluons with decay constants of order the weak scale, and therefore many collider signatures by heavy axions and saxions will show up at different energy scales. In particular, if the inferred broad decay width is due to multiple axions or saxions, a non-trivial peak structure may become evident when more data is collected. We also discuss cosmological implications of the aligned QCD axion scenario. In the Appendix we give a possible UV completion and argue that the high quality of the Peccei–Quinn symmetry is naturally explained in our scenario.